Prior Learning Assessment of Immigrants Competences—a Systematic Review - Britta Klages; Lea Sophie Mustafa (Journal of International Migration and Integration, 2022)
As immigration increases around the globe, the assessment and recognition of prior learning experiences become inevitable to incorporate foreign-trained professionals. However, even though Prior Learning Assessment and Recognition (PLAR) is claimed to be a source of social inclusion, it encourages a dividing practice—potentially building more barriers than bridges. This systematic review analyzes the practice of PLAR in the case of recent immigrants using 39 articles published between 1990 and 2020. The research reviewed was primarily conducted in Canada and Sweden, followed by other European countries. The systematic review synthesizes the context in which PLAR is used, the difficulties encountered during the process, and the impact of the process. By doing so, it pinpoints a new baseline for future innovative research. The analysis focuses on three identified difficulties: (1) language influence, (2) labour market demands, and (3) systemic limitations. The findings raise the question whether PLAR is an appropriate tool for the assessment of immigrants' prior learning, as the plurality in knowledge and education is not valued during the process. Therefore, overall systemic change is needed to enable social inclusion.
Keywords: 300; PLAR; Prior learning assessment and recognition; Immigrants